INTEGRATING UZBEK FOLK TALES INTO ENGLISH LANGUAGE LESSONS FOR 7TH GRADE STUDENTS USING MODERN METHODS - Madina Tashpulatova (Web of Journals Publishing, 2025)
This article analyzes innovative methods for integrating Uzbek folk tales into 7th-grade English language lessons. It also examines the linguistic and cultural features of colloquial phraseologisms in Uzbek and English. These studies aim to assist teachers in enhancing student engagement and developing their language skills during lessons.
Keywords: Uzbek folk tales, English language lessons, 7th grade, integration, innovative methods, information technologies, interactive games, creative writing, language learning, cultural consciousness.